O estudo da aplicação do planejamento estratégico e do sistema de informação gerencial para a tomada de decisão em instituições de ensino superior privadas de Teresina Piauí: um estudo de caso múltiplo - Silva, Helielton Teixeira Carvalho e (2012)
The present work studies the strategic planning tools (PE) and management information system (GIS) as mechanisms for decision making within the private institutions of higher education in Teresina-PI. We report the problems encountered in important areas of the HEI as the financial, academic and office/coordination, the possible solutions presented and its consequences, in order to minimize the difficulties experienced in everyday life of institutions on the use of budget planning, strategic and financial. Checks is what were the benefits that strategic planning and information system created for the private HEIs, through multiple case study and literature review on the subject, explaining basic concepts and classifications. The survey consisted of verifying that, with regard to private institutions of higher education organizations with demands and needs, and differentiated, the strategic plan and strengthen its performance GIS, generating information fast, efficient, accurate and especially useful to ensure a structuring differentiated management, improving the process of decision making by managers. The use of strategic planning became a necessity so that managers can better manage the GIS in an integrated way, as tools for making decisions and solving problems and difficulties experienced by private institutions, in order to achieve the goals and objectives proposed